The effects of acupuncture on rats with brain ischemiareperfusion - Kavakli, Ahmet; Köse, Evren; Akpolat, Nusret; Sarsilmaz, Mustafa (My University, 2009)
Objectives: To investigate the damage of brain ischemia-reperfusion (I/R) caused by occlusion of the middle cerebral artery (MCA), and the effects of acupuncture on this damage. Methods: This investigation took place in the Experimental Research Unit of Firat University, Elazig, Turkey in January-February 2007. For this aim, 14 rats were divided into 2 groups: I/R (control) and I/R+acupuncture (experiment). In the I/R group, the MCA was occluded for 60 minutes, after this reperfusion was applied. In the I/R+acupuncture group, dry needle acupuncture was applied after reperfusion for 10 days. At the end of the experiment, all rats were sacrificed. The brain tissues were examined after staining with hematoxylin and eosin. Results: In the samples belonging to the I/R group, widespread necrotic areas, red neurons, vacuolization, congestion, and edema were observed. In the I/R+ acupuncture group, the findings of ischemia were significantly decreased when compared with the I/R group. Conclusion: The damage caused by I/R was decreased by manual acupuncture therapy, however, further clinical studies are needed to determine the mechanism of acupuncture treatment, the optimal timing, and duration of acupuncture treatment in such disorders.
Keywords: acupuncture; animal experiment; animal model; animal tissue; article; brain edema; brain ischemia; brain necrosis; controlled study; histopathology; male; microscopy; middle cerebral artery occlusion; nonhuman; rat; reperfusion injury